Concrete Waste as a Cement Replacement Material in Concrete Blocks for Optimization of Thermal and Mechanical Properties - Rosman, M.S.; Abas, N.F.; Othuman Mydin, M.A. (EDP Sciences, 2014)
The sustainability of the natural environment and eco-systems is of great importance. Waste generated from construction forces mankind to find new dumping grounds and at the same time, more natural resources are required for use as construction materials. In order to overcome this problem, this study was conducted to investigate the use of concrete waste in concrete blocks with a special focus on the thermal and mechanical properties of the resulting products. Three varieties of concrete mixtures were prepared, whereby they each contained different amounts of concrete waste of 0%, 5% and 15%, respectively. These mixtures were formed into cube specimens and were then analysed for data on their compressive strength, density and ultrasonic pulse. Thermal investigations were carried out on each admixture as well as on a control concrete block of model design. The thermal data results indicated that the 15% concrete waste mixture had the lowest temperature in comparison to the surrounding air. For density and compressive strength, the highest readings came from the control mixture at 2390 kg/m3 and 40.69 N/mm2, respectively, at 28 days. In terms of pulse velocity, the 5% concrete waste mixture indicated medium quality results of 4016 m/s.